Evaluasi Program Gerakan Literasi Sekolah (GLS) di SD Negeri Salatuhur Kecamatan Anyar - Setiana Soleah; Rena Fadilah Malik; Anggi Riafadilah (STIT Fatahillah, 2022)
This research aims to find out the implementation of the School Literacy Movement (GLS) program at Salatuhur State Elementary School in Anyar District 2020 by using CIPP evaluation model. This research is evaluative research using a qualitative descriptive approach. Data collection techniques are carried out by observation, interview, and documentation methods. Analyze data using the Miles and Huberman Models with data reduction steps, data presentation, and conclusion drawing.The triangulation used is the source and method. The results showed that: (1) context evaluation (context) is in accordance with that put forward by Stufflebeam due to the legal basis of gls program implementation, gls program background, curriculum relevance and gls program objectives are in accordance with the expected competencies. (2) The evaluation of input (input) is in accordance with the submitted by Stufflebeam, due to the absence of students, program organizers, teachers, materials/teaching materials.But on indicators of the source of funds, and infrastructure facilities are still not appropriate.(3) Evaluation of process (process) there are some that have not been in accordance with the stated by Stufflebeam, namely on indicators of the use of learning media still with package books, notebooks, not yet using internet and computer facilities. In the indicator of library utilization is also not appropriate. Due to the lack of variatif collection of reading books, the number of visitors and interest in reading the library in 2020 decreased compared to the previous year.(4) Product evaluation there are some that are not in accordance with that put forward by Stufflebeam, especially on indicators of mastery of student material as well as student achievement in the field of literacy that is still few.